Sportwissenschaft - Knapik A (Dynamic Media Sales Verlag, 2014)
The functional efficiency of the physical motor system constitutes one of the basic factors creating welfare which according to WHO is synonymous to health. 171 men aged 30-60 were tested. The current and past levels of physical activity were determined in the research. Measurements of the range of the torsos three-plane mobility. An impact of a systematic physical activity on the level of the functional efficiency of the physical motor system, including suppleness, was established. The results of the research allowed the authors to conclude that doing sports professionally in youth brings about a generally higher level of flexibility in adulthood, even with a lack of physical activity, which seems to indicate the existence of the translocation effect.Key Words: flexibility, physical activity, translocation effect